PENGARUH PEMUPUKAN P TERHADAP PERTUMBUHAN PEGAGAN (Centella asiatica) DI INCEPTISOL DARI TOPOSEKUEN LERENG SELATAN GUNUNG MERAPI PADA BERBAGAI KONDISI LENGAS - , AGUS SUPRIHATIN, SP. ([Yogyakarta] : Universitas Gadjah Mada, 2011)
Inceptisols Merapi toposequent had potential as media of growth Centella asiatica, as developed from volcanic ash parent material rich in nutrients such as K, Ca, Na and Mg. The problems on the that soil was had a high P retention, so it were needed P fertilizer and water stress were expected to i ncreased the asiaticoside contents of Centella asiatica. The aims of this study to determine the effect of SP-36 fertilizer and moisture conditions as well as the best combination treatments of available P, P uptake and asiaticoside contents of Centella asiatica was grown in Inceptisols Merapi toposequent. This study was a pot experiment with Randomized Complete Block Design (RCBD) factorial with two factors and three replications. The treatments consisted of four doses of SP-36 were: 0, 75, 150 and 300 kg SP-36/ha, and 2 levels of moisture conditions that were 50% of field capacity and field capacity. The data were analyzed by analysis of variance (F-test) and continued with the DMRT test on level of significant 5%. The results showed that increasing doses of SP-36 fertilizer and moisture conditions was increasing available P after fertilization in Inceptisols Merapi toposequent. The best combination treatment that was at doses of 225 kg SP36/ ha and field capacity in Inceptisols Kalitirto gave the highest available P after fertilization that was equal to 44,13 ppm P.